BEYOND DISPOSABLE DESIGN: CHALLENGING PLANNED OBSOLESCENCE THROUGH CIRCULAR ECONOMY PRACTICES - Alivojvodic, Vesna (Economics of Agriculture, 2024)
The notion of obsolescence has transitioned from a naturally occurring phenomenon to a planned obsolescence, a strategic business model influenced by consumer demand, market forces, and technological progress. This paradigm began to take shape in the early 20th century and entails the production of pre-designed goods with a limited lifespan. Its widespread implementation has given rise to environmental degradation and increased waste generation. To tackle these challenges, we need to adopt responsible manufacturing practices. Currently, circular economy business models offer a chance to use more conscientious production methods. These methods focus on increasing output efficiency using fewer natural resources and materials. In addition, there is a focus on prioritising material reutilization and recyclability. This paper offers a detailed analysis of the development of planned obsolescence, including its historical evolution, causes, consequences and potential for modification of existing production practices to more fully implement the principles of the circular economy.